2021
DOI: 10.3389/fcell.2021.637873
|View full text |Cite
|
Sign up to set email alerts
|

Kinome-Wide RNAi Screen Uncovers Role of Ballchen in Maintenance of Gene Activation by Trithorax Group in Drosophila

Abstract: Polycomb group (PcG) and trithorax group (trxG) proteins are evolutionary conserved factors that contribute to cell fate determination and maintenance of cellular identities during development of multicellular organisms. The PcG maintains heritable patterns of gene silencing while trxG acts as anti-silencing factors by conserving activation of cell type specific genes. Genetic and molecular analysis has revealed extensive details about how different PcG and trxG complexes antagonize each other to maintain cell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 66 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…Recently we reported that BALL exhibits trxG like behavior by contributing to the maintenance of gene activation in flies ( Khan et al, 2021 ). Since BALL was shown to co-localize with Trithorax (TRX) at genes enriched with H3K27ac, we investigated if BALL binds to chromatin together with CBP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently we reported that BALL exhibits trxG like behavior by contributing to the maintenance of gene activation in flies ( Khan et al, 2021 ). Since BALL was shown to co-localize with Trithorax (TRX) at genes enriched with H3K27ac, we investigated if BALL binds to chromatin together with CBP.…”
Section: Resultsmentioning
confidence: 99%
“…Since BALL was shown to co-localize with Trithorax (TRX) at genes enriched with H3K27ac, we investigated if BALL binds to chromatin together with CBP. To this end, we analyzed ChIP-seq data of BALL ( Khan et al, 2021 ) and CBP ( Philip et al, 2015 ) from Drosophila S2 cells. Comparison of BALL and CBP binding to chromatin revealed their co-occupancy at 4577 genes ( Figure 1A and Supplementary Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations